Globalisation and the efficiency-equity trade-off - Roland Beck; Virginia Di Nino; Livio Stracca (European Central Bank (ECB), 2021)
We revisit the effects of globalisation over the past 50 years in a large sample of advanced and emerging countries. We use accessions to Clubs" (WTO, OECD, EU), financial liberalisation and an instrument for trade openness to study the trade-off between efficiency (proxied by real GDP per capita and TFP) and equity (proxied by the labour share of income and the Gini index of inequality). We find that (i) most of our episodes lead to an increase in trade openness (ii) effects on GDP per capita are mostly positive with some interesting exceptions and (iii) there is little evidence that globalisation shocks lead to more inequality.
Keywords: F13; F36; 330; globalisation; efficiency; equity; WTO; OECD; EU; financial liberalization; trade integration